Competitiveness and profitability of berries production in Jalisco - Lagunes-Fortiz, Edgar Ricardo; Lagunes Fortiz, Erika; Gómez-Gómez, Alma Alicia; Leos-Rodríguez, Juan Antonio; Omaña-Silvestre, José Miguel (Revista Mexicana de Ciencias Agrícolas, 2020)
During 2017, Jalisco was the second state with the highest contribution to the national agricultural GDP (SIAP, 2020). The cultivation of berries is an important socioeconomic activity in this state, which include cranberry (Vaccinium spp.), raspberries (Rubus idaeus) and blackberries (Rubus ulmifolius). Jalisco is the main producer of raspberry, the second of blackberry, and the fourth of strawberry (Fragaria spp.) at the national level (FIRA, 2016). However, it is perceived that unlike strawberry and blackberry crops, the cultivated area of raspberries increased in recent years, this increase cannot be explained by changes in price or yield but by other factors. The objective of the study was to determine if there were distortions in the markets that could have influenced the choice of producers in Jalisco for a particular type of berry. It was started from the hypothesis that of the berries, the raspberry had a greater competitive or comparative advantage. To measure the degree of market distortion, the methodology of the policy analysis matrix was applied. The results indicate that the three types of berries were profitable; however, some economic distortions benefited the raspberry and blackberry crops, and negatively impacted the strawberry crop, in addition there was a large subsidy to the profits of the raspberry crop. It is concluded that distortions created by the market and the government influenced the choice of the type of berry to be sown by producers, favoring raspberry production.